Penerapan Teknik Relaksasi Nafas dalam terhadap Tingkat Nyeri Persalinan Kala 1 Fase Laten - Rohmiasih Rohmiasih; Yuni Purwati (Lembaga Pengembangan Kinerja Dosen, 2026)
Irregular (inefficient) labor pain in the first stage can be fatal, causing prolonged labor (prolonged labor), severe stress for the mother (anxiety, fear), increased oxygen demand, circulatory changes (decreased placental perfusion), and the risk of acidosis in the mother and fetus, which can disrupt labor progress and endanger the mother and baby. Deep breathing relaxation is a technique that has been widely used in the context of stress and labor pain management. The purpose of this case report is to determine the effectiveness of applying breath relaxation on labor pain in the latent phase of the first stage of labor. The method used in this case study is a case report. This technique was performed in the latent phase of the first stage of labor, namely cervical dilation of 0–3 cm. The instrument used was the Numeric Rating Scale (NRS). The results of this study showed that after applying the deep breathing relaxation technique, the labor pain scale decreased from 6 (moderate pain) to 3 (mild pain). It can be concluded that the application of the deep breathing relaxation technique in laboring mothers in the latent phase of the first stage is effective in reducing the level of labor pain. This technique can be used as a non-pharmacological intervention that is safe, easy to implement, and in accordance with maternity nursing care standards.